Integrasi Kearifan Lokal Etnik Karo Sebagai Strategi Menjaga Ekosistem Mata Air di Hutan Sembahen - Ginting, Wendamia Hafni Br; Fijrina, Firly; Nurjannah, Siti; Pasaribu, Umy Wulandari Br; Saribu, Ruth Juliana Br Tambun; Berutu, Putri Harapani; Firmansyah, Wira (Jurnal Sains Sosio Humaniora, 2025)
The Karo ethnic group is one of the ethnic groups in North Sumatra that resides in the Karo Land. In Tanah Karo, there is a forest that serves as a source of life, namely Hutan Sembahen. Hutan Sembahen is a forest located in Desa Lau Solu, Kecamatan Mardinding, and it contains springs. Hutan Sembahen is protected through the local wisdom of the Karo ethnic group. This local wisdom can preserve the springs so that the water ecosystem remains unpolluted. This research aims to (1) analyze the integration of Karo ethnic local wisdom in Desa Lau, Kecamatan Mardinding as a strategy to maintain the water ecosystem in the Hutan Sembahen area and (2) examine the utilization of springs in the Hutan Sembahen area in accordance with SDG 6. This type of research uses qualitative methods that adopt an ethnographic approach. The research location is Lau Solu Village, Mardinding District, Karo Regency. Research data were collected through participatory observation, ethnographic interviews, and literature studies. The research data analysis uses Spradley's ethnographic analysis techniques, namely ethnographic interview analysis, domain analysis, and taxonomy analysis.